AB1029 Genistein prevents quality of life osteopenic post-menopausal womens: A 2-year randomized, double-blind, controlled-study. (23rd January 2014) - Atteritano, M.; Miceli, G.; Bagnato, G.; Sangari, D.; Talotta, R.; Tamburello, A.; Morgante, S.; Bagnato, G.
Abstract : Background: Postmenopausal estrogen decline is implicated in several age-related physical and psychological changes in women, including decreases in perceived quality of life (QoL). A number of trials with hormone therapy showed beneficial effects of the intervention on parameters of quality of life. However, because of known or suspected serious side-effects of conventional hormone therapy there is a need for alternatives Objectives: The goal of this study was to evaluate the effect of genistein treatment on health-related quality of life in osteopenic postmenopausal women. Methods: We conducted a double-blind randomized placebo-controlled trial with phytoestrogen genistein 54 mg or placebo for 2 year. For this trial, we recruited 288 postmenopausal women aged 49 to 67 years. At baseline, after 1 year and at final visit, participants filled in the Short Form of 36 questions (SF-36), the Questionnaire on Life Satisfaction Modules (QLS M ), and the Zung Self-Rating Depression Scale (ZSDS). Results: For the placebo group scores on all dimensions of the SF-36 and the QLS M decreased after 1 year and after 2 years. The genistein group showed increases on all dimensions of the SF-36 and the QLSM. There were however statistically significant differences in changes of scores between the two intervention groups. For the ZSDS similarly, significant differences were found between the groups. Conclusions: In conclusion, the findings in this randomized trial do support the presence of a marked effect of phytoestrogen genistein on quality of life (health status, life satisfaction, and depression) in osteopenic postmenopausal women. References: Herschbach P, Henrich G, Strasburger CJ, et al. Development and psychometric properties of a disease-specific quality of life questionnaire for adult patients with growth hormone deficiency. Eur J Endocrinol 2001;1453:255–265. Blumel JE, Castelo-Branco C, Binfa L, et al. Quality of life after the menopause: a population study. Maturitas 2000;341:17–23. Ravnikar VA. Compliance with hormone replacement therapy: are women receiving the full impact of hormone replacement therapy preventive health benefits? Women Health Iss 1992;22:75–80. Writing Group for the Women's Health Initiative Investigators (2002) Risks and benefits of estrogen plus progestin in healthy postmenopausal women: principal results From the Women's Health Initiative randomized controlled trial. JAMA 288 (3):321–333 Zung, WW (1965). A self-rating depression scale. Archives of General Psychiatry 12: 63–70. Disclosure of Interest: None Declared